Preparation of activated nanocarbon from different variety of rice straw for fermentative hydrogen production from alkali spent treated rice straw hydrolyzate - Srivastava N.; Khan P.A.; Lal B.; Singh R.; Ahmad I.; Mishra P.K. (My University, 2025)
Renewable carbon-based catalyst development is a promising approach towards sustainable and low-cost biohydrogen production from lignocellulosic waste. In this study, being a rich source of cellulose, different varieties of rice straw (RS) have been used to fabricate activated carbon-based catalysts (ACBCs) using facile, low-cost pretreatment methods and also for biohydrogen production. The water soaking and sonication processes, followed by calcination, are applied to produce ACBCs, which have been characterized by different techniques to probe physicochemical characteristics. The impact of ACBCs was observed on cellulase enzyme production through solid state fermentation (SSF), which exhibited the highest 15 IU/gds FPA at 12 h using 1.0 % ACBCs-treated fermentation medium and was found to be significantly improved as compared to control. The produced crude enzyme was thermally stable at 50 °C up to 15 h, reflecting its 54 % half-life, while at 55 °C, a 56 % half-life up to 10 h was noticed. Consequently, enzymatic hydrolysis of alkali pretreated RS produced 34 g/L sugar in 24 h, and it produced cumulative biohydrogen of 2745 mL/L at 50 h of dark-fermentation. © 2024 Hydrogen Energy Publications LLC